Lipids in the tumor microenvironment: immune modulation and metastasis - Pascual, Gloria; Benitah, Salvador Aznar (Frontiers in Oncology, 2024)
Tumor cells can undergo metabolic adaptations that support their growth, invasion, and metastasis, such as reprogramming lipid metabolism to meet their energy demands and to promote survival in harsh microenvironmental conditions, including hypoxia and acidification. Metabolic rewiring, and especially alterations in lipid metabolism, not only fuel tumor progression but also influence immune cell behavior within the tumor microenvironment (TME), leading to immunosuppression and immune evasion. These processes, in turn, may contribute to the metastatic spread of cancer. The diverse metabolic profiles of immune cell subsets, driven by the TME and tumor-derived signals, contribute to the complex immune landscape in tumors, affecting immune cell activation, differentiation, and effector functions. Understanding and targeting metabolic heterogeneity among immune cell subsets will be crucial for developing effective cancer immunotherapies that can overcome immune evasion mechanisms and enhance antitumor immunity.